Another world is possible? – Climate movements’ bounded politicization between science and politics - Pavenstädt, Christopher N. (Frontiers in Political Science, 2024)
How we have come to think about climate futures has predominantly been shaped by science- and expert-driven assessments. As research turns to the role of future visions as a driver of social change and overcoming political gridlock, political struggles are understood as conflicts over making (alternative) desirable futures socially performative. The recent advent of the new climate movements (NCMs) has given rise to the assumption that they could contribute to a re-politicization of climate politics by introducing alternative future visions. Their names and slogans articulate future expectations, such as futures “worth studying for” (Fridays for Future) or averting extinction (Extinction Rebellion). Yet, research on the politicizing qualities of the NCMs is inconclusive. I use a new framework for examining (de-)politicization dynamics to study public communication of German factions of both movements from 2019 to 2022. The results underscore climate movements’ strong affiliation to science from their inception, yet over time, increasing attempts to adhere to principles of climate justice. However, climate movements still struggle to re-politicize climate futures beyond dominant positive visions of modernization and negative visions of collapse. I argue that this bounded politicization is indicative of the broader discursive dynamics that have weakened the ability to formulate alternative visions and discuss to what extent the centrality of scientific imaginative logics and understandings of the science–policy interface act to inhibit the articulation of alternative visions.